Hubungan Rasa Kesepian dengan Kecenderungan Adiksi Sosial Media Platform Instagram dan Tiktok pada Perempuan Remaja Akhir - Arsih, Laudina Swasti; Sari, Woro Apriliana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The development of information and communication technology has increased the use of social media among adolescents, especially the Instagram and TikTok platforms. The increased intensive use of social media among adolescents is often not only functional, but also compulsive, which can lead to social media addiction behavior. Loneliness is one of the psychological factors that contribute to the emergence of social media addiction behavior, especially on immersive and interactive platforms such as TikTok and Instagram. This study aims to analyze the relationship between loneliness and social media addiction tendencies in late adolescent women. The research method uses a quantitative approach with puposive sampling method. The number of samples obtained was 152 respondents with an age range of 18-24 years. Data were analyzed using the Spearman correlation test with SPSS version 25. The results obtained a correlation coefficient value of 0.215 with a significant level of 0.008 (p < 0.01). This value shows that there is a significant positive relationship between loneliness and the tendency of social media addiction.